A Study on Coupling Index of Graphs - A. Revathi,D. Christia Jebakumari J. Vijaya Xavier Parthipan, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
A range of fields, including chemistry, economy, gadgets, business analysis, social sciences,and medical, will always benefit from different topological indices. The computation of the graph coupling index and coupling distance